2008
DOI: 10.1002/ana.21308
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TPM3 are a common cause of congenital fiber type disproportion

Abstract: Mutation of TPM3 is the most common cause of CFTD reported to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(88 citation statements)
references
References 26 publications
3
84
1
Order By: Relevance
“…This condition, however, is genetically heterogeneous and has been observed in several forms of congenital myopathies, neuromuscular disorders, and muscular dystrophies (Clarke and North 2003). Mutations in ACTA1 (Laing et al 2004), SEPN1 (Clarke et al 2006), TPM3 (Clarke et al 2008), RYR1 (Wilmshurst et al 2010), and more recently MYH7 (Ortolano et al 2011) have also been identified in patients with FTD. To add to its nonspecific nature, this morphological finding has been reported in association with several inherited metabolic disorders including Pompe disease (Martin et al 1976), multiple sulfatase deficiency (Tachi et al 1984), congenital lactic acidosis (Iso et al 1993), metachromatic leukodystrophy (Krendel et al 1994), carnitine palmitoyltransferase deficiency (Shintani et al 1995), and Krabbe disease (Marjanovic et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This condition, however, is genetically heterogeneous and has been observed in several forms of congenital myopathies, neuromuscular disorders, and muscular dystrophies (Clarke and North 2003). Mutations in ACTA1 (Laing et al 2004), SEPN1 (Clarke et al 2006), TPM3 (Clarke et al 2008), RYR1 (Wilmshurst et al 2010), and more recently MYH7 (Ortolano et al 2011) have also been identified in patients with FTD. To add to its nonspecific nature, this morphological finding has been reported in association with several inherited metabolic disorders including Pompe disease (Martin et al 1976), multiple sulfatase deficiency (Tachi et al 1984), congenital lactic acidosis (Iso et al 1993), metachromatic leukodystrophy (Krendel et al 1994), carnitine palmitoyltransferase deficiency (Shintani et al 1995), and Krabbe disease (Marjanovic et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of several families with severe, intermediate and typical NM forms have identified mutations in α-tropomyosin (TPM3) and beta-tropomyosin [19][20][21] . A recent study described an Australian familly with a mutation in the TPM3 gene 22 .…”
Section: Fig 1 Hematoxilin-eosin (He) Stain Showing Variation In Fibmentioning
confidence: 99%
“…To date, defects in six distinct genes have been identified in cases of NM. These include mutations in α-tropomyosin (TPM3), betatropomyosin (TPM2), nebulin (NEB), α-actin (ACTA1), cofilin2 (CFL2) and troponin T (TNNT1) 4,[17][18][19][20][21][22][23][24][25][26][27][28] . This study describes the clinical manifestations of nemaline myopathy using histochemical analysis along with expression analysis of nebulin, desmin and myosin proteins with immunohistochemistry.…”
mentioning
confidence: 99%
“…TPM2 is expressed in both slow (type 1), and, to a lesser extent, fast (type 2) muscle fibres, whereas TPM3 encodes the slow-specific isoform aTm slow . 25 Mutations in slow muscle fibre-specific TPM3 cause NM 6,13,17,18,26 and have recently been shown to perhaps be a relatively common cause of congenital fibre type disproportion (CFTD), 27 while mutations of TPM2, expressed in all muscle fibres, have been reported in patients either with NM, 7 distal arthrogryposis, 28 or cap disease. 29 TPM1 mutations are known to cause dilated and hypertrophic cardiomyopathies (MIM 115196).…”
Section: Discussionmentioning
confidence: 99%